Estudo fitoquímico de Baccharis myriocephala e avaliação sobre a liberação de mediadores pró-inflamatórios. - Patrícia Gardênia Assis Souza (2022)
Medicinal plants are widely used as home remedies or as an alternative and/or complementary treatment due to the variety of chemical constituents. The genus Baccharis (Asteraceae) stands out for its popular use for pain relief, for the treatment of gastrointestinal diseases and as an anti-inflammatory agent. Some Baccharis species are known in the literature for therapeutic actions attributed to phenolic acids, flavonoids and terpenes. Thus, this genus is considered a promising source for the development of new therapeutic agents with anti-inflammatory action. In the present work, the study of the in vitro anti-inflammatory potential of some species of this genus and the phytochemical study of B. myriochepala were carried out. After a screening process regarding the evaluation of the effect of the extracts on the release of the pro-inflammatory mediators TNF, IL-1β and IL-6 in THP-1 cells stimulated by LPS in vitro, it was observed that the ethanolic extract of aerial parts from B. myriocephala significantly reduced the release of these mediators at a concentration of 30 μg/mL. In this context, the fractionation and isolation of substances through chromatographic techniques followed. From the fraction obtained in ethyl acetate, two flavones were isolated and identified, hispidulin and cirsimaritin, characterized by NMR, using 1D (1H and 13C) and 2D (HSQC and HMBC) experiments. The two isolated compounds were evaluated in vitro for their effects on the release of IL-1β at concentrations at 3, 10 and 30 μM. Hispidulin had maximum inhibition at 10 μM, reducing the release of IL-1β by 57.1 ± 16.3%, while cirsimaritin inhibited the release of this cytokine by 69.8 ± 4.3% when evaluated at the same concentration. In conclusion, the study resulted in the identification of two flavones from the ethanolic extract of aerial parts of B. myriocephala, with potential anti-inflammatory activity.